Accountability of Policing - Lister, Stuart ; Rowe, Michael (Routledge, 2020)
This book makes a significant contribution to the literature on accountability for policing in three particular ways. First it adopts much broader conceptions of both accountability and 'policing’ than have been evident in almost all the previous literature on this topic. Second, it is historically grounded, which enhances understanding of where things stand today. Third, it is thoroughly up to date, exploring new conceptual frames, the most recent developments, and the most recent critiques. For all these reasons, it is a book that should be read by anyone who is interested, for whatever reasons, in its central subject.